SUPERVISION OF LAND CLEARING BY BURNING ACCORDING TO THE WORK CREATION LAW - Triono Eddy; Vita Cita Emia Tarigan (Journal of Islamic, Social, Economics and Development, 2023)
Land clearing by burning is a common agricultural practice in Indonesia. However, this practice can cause negative impacts such as air pollution and forest fires which endanger the environment and the health of humans and wildlife. Therefore, supervision of land clearing by burning is very important to protect the environment and public health. The Job Creation Law, or the Omnibus Law, has several articles related to monitoring land clearing by burning. Article 116 states that everyone is obliged to protect and preserve the environment. In addition, Article 117 stipulates that the government, communities and entrepreneurs are required to control forest and land fires. Whereas, Law Number 32 of 2009 and Law Number 39 of 2014 also regulate land clearing by burning and provide strict sanctions for perpetrators of forest fires. More serious and effective prevention and handling efforts need to be carried out by the government, the community, and all relevant stakeholders to reduce and overcome this problem. One way is to increase supervision of land clearing practices that are not in accordance with the rules and provide strict sanctions for perpetrators of forest fires. In addition, socialization and education is needed for the community about the importance of preserving the environment and not taking actions that damage the environment. In this case, the role of society, especially farmers,